Duodenal bleeding in a patient with Covid-19-Related Acute Respiratory Distress Syndrome - Maurizio Gabrielli; Laura Franza; Maria Chiara Bungaro; Tommaso de Cunzo; Alessandra Esperide; Federico Valletta; Irene Gasparrini; Luca Santarelli; Alessio Migneco; Lorenzo Capaldi; Francesco Franceschi (Archive of Gerontology and Geriatrics Research - Peertechz Publications, 2020)
High incidence of thrombotic complications was observed in patients with Acute Respiratory Distress Syndrome (ARDS) related to Coronavirus Disease 2019 (COVID-19) [1]. The pathophysiology seems related to systemic thrombophilia by hyper-immune reaction, inducing a "cytokine storm" [1].